Frames of Al-Alam TV channel’s handling of the Iraqi and Lebanese protests Analytical study of the main news bulletin for the period from October 1, 2019, to December 31, 2019 - al-Musawi, Muhammad Muhyi Abd al-Amir; Al-Kinani, Mohsen Glubb (ALBAHITH ALALAMI, 2022)
In October 2019, Iraq and Lebanon witnessed widespread protests, which aroused the interest of the media, as they began with demands for the provision of services, then escalated with the overthrow of the political system. The researchers chose a satellite channel that represents a direction for a country accused of entering the line of protests. This paper aims to analyze the main bulletin of Al-Alam channel to find out how it deals with the protests in the news. It is classified descriptively, using the survey method and the method of content analysis. The study community was represented by the main news bulletin of Al-Alam channel. The researchers adopted a deliberate sample for the period from 1/10/2019 to 31/12/2019, as the bulletin intensified its coverage of the protests. The research reached a number of results, the most important of which are: framing the news about the protests within the framework of responsibility, and confirming that the demonstrators attacked property and security forces.